Anaesthetic complications in plastic surgery - Soumya Sankar Nath; Debashis Roy; Farrukh Ansari; Sundeep T. Pawar (Indian Journal of Plastic Surgery)
Anaesthesia related complications in plastic surgeries are fortunately rare, but potentially catastrophic. Maintaining patient safety in the operating room is a major concern of anaesthesiologists, surgeons, hospitals and surgical facilities. Circumventing preventable complications is essential and pressure to avoid these complications in cosmetic surgery is increasing. Key aspects of patient safety in the operating room are outlined, including patient positioning, airway management and issues related to some specific conditions, essential for minimizing post-operative morbidity. Risks associated with extremes of age in the plastic surgery population, may be minimised by a better understanding of the physiologic changes as well as the pre-operative and post-operative considerations in caring for this special group of patients. An understanding of the anaesthesiologist′s concerns during paediatric plastic surgical procedures can facilitate the coordination of efforts between the multiple services involved in the care of these children. Finally, the reader will have a better understanding of the perioperative care of unique populations including the morbidly obese and the elderly. Attention to detail in these aspects of patient safety can help avoid unnecessary complication and significantly improve the patients′ experience and surgical outcome.